A case of metastatic urinary bladder tumor from gastric carcinoma - Nakamura, K (Hinyokika kiyo. Acta urologica Japonica, 1992)
We report a case of metastatic bladder tumor from gastric carcinoma. A 55-year old male patient was referred to our urological clinic with a complaint of frequent urination and voiding pain. He had undergone total gastrectomy for poorly differentiated adenocarcinoma, signet-ring cell type, 9 months earlier. Computed tomographic scan revealed a thick bladder and rectum wall all around. Punch biopsies from vesical and rectal wall revealed metastatic adenocarcinoma, signet-ring cell type. There were no other metastatic sites. Systemic chemotherapy was done with a combination of mitomycin-C, 5-fluorouracil and cytosine arabinoside. This chemotherapy was effective and complete remission was obtained at bladder and rectum. Six months after chemotherapy, peritoneal recurrence developed and he died 9 months after chemotherapy. However no recurrence of bladder tumor was detected. This was a quite rare case of metastatic bladder tumor characterized by good response to systemic chemotherapy